GE_GERICHTE C/9514/2015 vom 22. Mai 2017 - GE Cour de justice (2017)
BAIL À FERME ; CLAUSE PÉNALE ; INTERPRÉTATION(SENS GÉNÉRAL) ; AUTORISATION D'EXPLOITER ; RÉSILIATION ; NOUVEAU MOYEN DE FAIT | CO.275ss; CO.285; CO.160; CO.163;